Clinical Supervision in Nursing: the (un)Known Phenomenon - Cruz, Sandra (2012)
To implement a clinical supervision model in nursing, we carry out an exploratory, descriptive and longitudinal study. We aim to publicize the results of its first phase which was focused on the chief nurses’ opinion on the clinical supervision on nursing (CSN) phenomenon. Interviews to all chief nurses (18) were conducted. Content analysis was used to data analysis. Themes and categories were found such as perspectives, relevance, conditions to CSN, among others. Results suggested that chief nurses need to improve their knowledge on CSN. However, it was clear what CSN is not or should not be to some of them.